Comprehensive optical design model of the goldfish eye and quantitative simulation of the consequences on the accommodation mechanism. (January 2019) - Claus, Ilka; Frey, Katharina; Hönle, Tobias; Brüning, Robert; Reichenbach, Andreas; Francke, Mike; Brunner, Robert
Abstract: To further extent our understanding of aquatic vision, we introduce a complete optical model of a goldfish eye, which comprises all important optical parameters for the first time. Especially a spherical gradient index structure for the crystalline lens was included, thus allowing a detailed analysis of image quality, regarding spot size, and wavelength dependent aberration. The simulation results show, that our realistic eye model generates a sufficient image quality, with a spot radius of 4.9 μm which is below the inter cone distance of 5.5 μm. Furthermore, we optically simulate potential mechanical processes of accommodation and compare the results with contradictory findings of previous experimental studies. The quantitative simulation of the accommodation capacity shows that the depth of field is strongly dependent on the resting position and becomes significantly smaller when shorter resting positions are assumed. That means, to enable an extended depth perception with high acuity for the goldfish an adaptive, lens shifting mechanism would be required. In addition, our model allows a clear prediction of the expected axial lens-shift, which is necessary to ensure a sufficient resolution over a large object range.